Analysis of bacterial diversity and functional differences of Jiang-flavored Daqu produced in different seasons - Lamei Wang; Yuxin Cheng; Xiaoxia Hu; Yongguang Huang (Frontiers in Nutrition, 2023)
High-temperature Daqu is an important saccharifying fermenting starter for brewing Jiang-flavored Baijiu. This paper analyzed the diversity characteristics of bacterial communities of Jiang-flavored Daqu (JFDQ) with seasonal changes through Illumina HiSeq sequencing and multivariate statistical methods. Results showed that 21 phyla, 529 genera, and 47 core bacterial genera were identified from the 48 composite samples. Among them, eight functional genera were only found in the summer-produced Daqu (Propionigenium, etc.). Pantoea, Bacillus, Lentibacillus, and Oceanobacillus, respectively, served as the representative functional bacterial genera of the four seasons. Functional prediction analysis showed that Amino acid metabolism Carbohydrate metabolism, Lipid metabolism, Metabolism of cofactors and vitamins, and Nucleotide metabolism (relative abundance > 1%) were the most critical microbial functions in JFDQ, and these key enzymes involved in acetoin biosynthesis, and acetyl-CoA biosynthesis were more abundant in the summer than in the winter. The functional microorganisms community in this paper would provide valuable suggestions about the seasonal production of JFDQ, guiding the Baijiu brewing processes.